Interventions in Improving Spiritual Well-Being: A Scooping Review - Alaidin, Makdum; Andriany, Megah; Dewi, Nur Setiawati (Indonesian Journal of Global Health Research, 2024)
Spiritual well-being has an important role for individuals in dealing with mental health problems and quality of life. The aim of this research is to explore various interventions to improve individual spiritual well-being to help overcome difficult situations, reduce stress and help achieve balance in life. Methodology: This research adopts an approachscoping review with the framework developed by Arksey and O'Malley. Research includes searching articles through databases Google Scholar and Spingerlink with the keyword "Spiritual well-being"AND"Intervention." Results: Research using the PRISMA method with data sources from Google Scholar and Spingerlink produced a total of 20,348 articles. The articles were then filtered based on the inclusion criteria, namely using English with a range of 2018-2023 regarding interventions to improve spiritual well-being which resulted in 14 articles that met the requirements. Conclusion: Research shows that there are 6 (six) interventions in the form of spiritual counseling, psychospiritual intervention, spiritual care intervention, mindfulness intervention, spiritual group therapy and music therapy which have been proven to improve spiritual well-being. These interventions have been shown to be important in addressing spiritual distress and improving spiritual well-being, which can accelerate mental health recovery and achieve spiritual well-being.